Crystallization behavior of iron‐ and boron‐containing nepheline (Na2O·Al2O3·2SiO2) based model high‐level nuclear waste glasses. Issue 3 (1st August 2018) - Deshkar, Ambar; Ahmadzadeh, Mostafa; Scrimshire, Alex; Han, Edmund; Bingham, Paul A.; Guillen, Donna; McCloy, John; Goel, Ashutosh
Abstract: This study focuses on understanding the relationship between iron redox, composition, and heat‐treatment atmosphere in nepheline‐based model high‐level nuclear waste glasses. Glasses in the Na2 O–Al2 O3 –B2 O3 –Fe2 O3 –SiO2 system with varying Al2 O3 /Fe2 O3 and Na2 O/Fe2 O3 ratios have been synthesized by melt‐quench technique and studied for their crystallization behavior in different heating atmospheres—air, inert (N2 ), and reducing (96%N2 –4%H2 ). The compositional dependence of iron redox chemistry in glasses and the impact of heating environment and crystallization on iron coordination in glass‐ceramics have been investigated by Mössbauer spectroscopy and vibrating sample magnetometry. While iron coordination in glasses and glass‐ceramics changed as a function of glass chemistry, the heating atmosphere during crystallization exhibited minimal effect on iron redox. The change in heating atmosphere did not affect the phase assemblage but did affect the microstructural evolution. While glass‐ceramics produced as a result of heat treatment in air and N2 atmospheres developed a golden/brown colored iron‐rich layer on their surface, those produced in a reducing atmosphere did not exhibit any such phenomenon. Furthermore, while this iron‐rich layer was observed in glass‐ceramics with varying Al2 O3 /Fe2 O3 ratio, it was absent from glass‐ceramics with varying Na2 O/Fe2 O3 ratio. An explanation of these results has been provided on the basis of kinetics of diffusion of oxygen and network modifiers in the glasses under different thermodynamic conditions. The plausible implications of the formation of iron‐rich layer on the surface of glass‐ceramics on the chemical durability of high‐level nuclear waste glasses have been discussed.